2012
DOI: 10.1111/j.1750-3841.2012.02651.x
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐based Edible Coatings for Quality Preservation of Postharvest Whiteleg Shrimp (Litopenaeus vannamei)

Abstract: The main practical application behind the development of chitosan (CH) and O-carboxymethyl chitosan (CMC) used to preserve postharvest whiteleg shrimp lies with the fact that these polysaccharides represent a renewable source of natural biodegradable polymers and meet with the emergence of more and more food safety problems. Both CMC and CH can be used as food preservatives to extend shrimp shelf life. However, CMC is more convenient due to its solubility. In the future, CMC will be used in the food processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
65
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 40 publications
13
65
2
2
Order By: Relevance
“…The present results are in agreement with those of Huang et al (2012) who reported that the application of chitosan coatings was effective in retarding melanosis of shrimp during storage. The retarding of melanosis in shrimp treated by chitosan coating may be attributed to certain chitosan functional properties, such as being an antioxidant, an antimicrobial agent, and an oxygen barrier (Huang et al, 2012). Additionally, GTE + chitosan coating was more effective than chitosan coating or GTE alone in retarding of melanosis in shrimp, suggesting that there was a synergistic effect between chitosan coating and GTE.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The present results are in agreement with those of Huang et al (2012) who reported that the application of chitosan coatings was effective in retarding melanosis of shrimp during storage. The retarding of melanosis in shrimp treated by chitosan coating may be attributed to certain chitosan functional properties, such as being an antioxidant, an antimicrobial agent, and an oxygen barrier (Huang et al, 2012). Additionally, GTE + chitosan coating was more effective than chitosan coating or GTE alone in retarding of melanosis in shrimp, suggesting that there was a synergistic effect between chitosan coating and GTE.…”
Section: Resultssupporting
confidence: 93%
“…It agrees with those of Huang et al (2012) and Wu (2014) who reported that a lower increase in TVB-N value was obtained in the shrimps treated by chitosan coating. Additionally, Figure 3.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations